PENGEMBANGAN BUKU PENGAYAAN BIOLOGI BERBASIS LITERASI SAINS BAGI SISWA SMA - Prasono, Awanda; Natalina L, Mariani; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research aims to provide a literacy-based biological enrichment book of science for high school students. The research consists of the stages of analysis, design, and development. This enrichment books developed based on analysis of the PISA 2006 year reserved grain and 2015 as well as linkages with basic competency curriculum 2013. The stage of the analysis, design, development, validation and internal tests I carried out in the laboratory of Biology education FKIP University of Riau. External validation and testing II implemented in SMA Negeri 1 Pekanbaru. Enrichment books validated on three aspect include format, the appropriateness of the content and science literacy, as well as language. Enrichment books produced in this research is at a very valid category and very good so worth is used as a source of independent study ability of students in developing science literacy.Keywords : Enrichment books, science literacy, high school students